Association of pet ownership with eating, exercise, nutritional status, and heart health of seniors - Dembicki, Diane Florence, author; Anderson, Jennifer, advisor; Melby, Chris, advisor; Stallones, Lorann, committee member; Auld, Garry, committee member; Barber, Clif, committee member (Colorado State University. Libraries, 1995)
The familiar adage "pets are good for your health" is an interesting but largely untested theory. Numerous anecdotal remarks on the health benefits of companion animals to the elderly refer to eating and exercise. Research is needed to examine if any health benefits result from pet ownership, and, if so, models must be developed to explain the reasons. An early empirical study found increased survival rate of heart patients due to pets (Freidmann et al., 1980). A theoretical framework is developing based on pet attachment and substitute social support (Stallones et al., 1990). Recent research investigated the effects of pets on risk factors for cardiovascular disease (Anderson et al., 1992). A new model was developed, based on pet ownership leads to better self care, to show possible associations between pet ownership with eating, exercise, nutritional status, and specific cardiovascular risk factors. The major hypotheses tested were pet owners have significantly lower serum total cholesterol, low-density lipoprotein cholesterol, and triglycerides, and higher high-density lipoprotein cholesterol than non-owners and these differences are explained by diet and physical activity. The experimental design was a cross-sectional, observational study of a self-selected convenience sample. Seniors aged sixty and above were solicited at senior congregate meals program sites in north-central Colorado (n=127). Instruments used were questionnaires on eating and exercise, emotional and physical health, social support, and pet attachment, biochemical analyses of diet and blood, and anthropometric and physiological measures. Statistical procedures included two-tailed t-tests, Chi-square, multivariate analysis, correlation coefficients and partial coefficients, and analysis of covariance ; a value of p <0. 05 was considered significant. There were few significant differences in diet, nutritional status, and risk factors for cardiovascular disease and no significant differences in number of exercise activities and duration of walking between pet and nonowners. Dog owners walked significantly longer than nonowners. Pet owners had significantly lower triglycerides than non-owners. It could not be concluded that pet ownership is associated with better diet and nutritional status, greater physical activity, and reduced cardiovascular risk compared to non-ownership in seniors.
Keywords: Older people -- Health and hygiene; Human-animal relationships; Pet owners